Designs for small spaces. - Hudson, Jennifer, ....- (London : Laurence King, 2010)
Small space living is no longer a lifestyle choice but a necessity in most cities, where property is expensive and space is at a premium. Designs for Small Spaces brings together over 500 cleverly designed products suitable for small spaces, and includes full details on where the products can be sourced.